FAKTOR-FAKTOR PENILAIAN KEPUTUSAN KONSUMEN DALAM PEMBELIAN KOSMETIK HALAL (STUDI KASUS MAHASISWI MUSLIMAH FAKULTAS EKONOMI DAN BINIS UNIVERSITAS AIRLANGGA) - Mega Fitria Sitama; Eko Fajar Cahyono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the assessment of prices, income, benefits, priority scale, perceptions of wasteful feelings and consumer decisions in purchasing halal cosmetics case studies of Unair Surabaya FEB female students. This study uses a quantitative approach with analysis of hypothesis testing. Retrieval of primary data in this study was conducted using a questionnaire. The sample in this study amounted to 357 students from the Faculty of Economics and Business, Airlangga University, Surabaya. Based on the results of the study, the valuation of prices consisting of prices (benefits), prices (affordable), prices (competing) partially has a significant effect. Revenue partially has a significant effect. Halal judgments which consist of halal necessity, halal logo (competitor), halal logo (Islamic rules), halal logo (important aspects) partially have a significant effect. Assessment of benefits that consist of benefits (face), benefits (appearance), benefits (not allergies), benefits (long-term), partially significant effect. Evaluation of priority scale consists of priority scale (food), priority scale (health), priority scale (education), priority scale (residence) partially significant effect. Perception assessment consisting of perceptions (unique and funny packaging), perceptions (replace new ones), perceptions (moderate trends), partially have a significant effect. Consumer decision making partially has a significant effect.Keywords: Price valuation, Income, Benefits, Priority Scale, Perception of Wasteful Feelings, Consumer Decisions, Halal Cosmetics.REFERENCESAbdullah, Thamrin dan Francis Tantri. 2012. Manajemen Pemasaran. Jakarta: PT. Raja Grafindo Persada.Alhafidz, Ahsin W. 2007. Fikih Kesehatan. Jakarta: AmzahEngel, James F ., et al. 1994. Perilaku Konsumen Jilid 1 hal 69. Jakarta:Binarupa AksarJuliana Ibnu Mubarok. 2012. Kamus Istilah Ekonomi. Bandung: Yrama WidyaKarim, Adi warman. 2012. Ekonomi Mikro Islam. Jakarta: Rajawali Press (https://kemenag.go.id/berita/read/302900, diakses 12 september 2018Kotler, philip dan kevin lane keller. 2003. Manajemen Pemasaran Edisi 13 terjemahan Bob Sabran. Jakarta: ErlanggaMuflih, Muhammad. 2006. Perilaku Konsumen dalam perspektif Ilmu Ekonomi Islam. Jakarta: PT.Raja Grafindo. Muhammad. 2004. Ekonomi Mikro dalam Perspektif Islam. Yogyakarta : BPFE YogyakartaNasution, Mustafa Edwin et al. 2006.  Pengenalan Eksklusif Ekonomi Islam. Jakarta: Kencana Prenadamedia GroupQardhawi, Yusuf. 2000.Halal dan Haram dilengkap Takhrij Hadits.Jakarta : Robbani PressRakhmat, Jalaludin. 2007.  Psikologi komunikasi. Bandung PT Remaja Rosdakarya.Rosyidi, Suherman. 2014. Pengantar Teori Ekonomi Pendekatan kepada Teori Ekonomi Mikro & Makro. Jakarta: Raja Grafindo PersadaSari, Tiurma Yustisi. 2009. Hubungan antara Perilaku Konsumtif dengan Body Image pada Remaja Putri. Skripsi S1. Sumatera Utara: Universitas Sumatera Utara.Setiadi, Nugroho J. 2013. Perilaku Konsumen. Jakarta: Kencana Prenada Media Group.Setyaningrum, Ari., et al. 2015. Prinsip-Prinsip Pemasaran Plus Tren Terkini. Yogyakarta: Andi OffsetSitepu, Novi Indriyani. 2016. Jurnal Perspektif Ekonomi Darussalam. Volume 2 No 1 hal 13. ISSN 2502-6976Slameto. 2010. Belajar & Faktor-Faktor yang  Mempengaruhi. Jakarta: Rineka CiptaSondang, P Siagaan. 1989. Teori Motivasi dan Aplikasinya. Jakarta :Rineka CiptaSudremi, Yuliana. 2007. Pengetahuan Sosial Ekononomi Kelas X. Jakarta: Bumi AksaraSunyoto, Danang. 2013. Dasar-Dasar Manajemen Pemasaran. Yogyakarta: CAPSSyarifuddin, Amir. 2011.Ushul Fiqh Jilid 2. Jakarta : KencanaTjiptono, Fandy. 2006. Pemasaran Jasa hal 2. Malang : Bayumedia PublishingTodaro. 2002. Ekonomi Dalam Pandangan Modern. Jakarta : Bina AksaraWorld Halal Forum, 2013. (http://www.worldhalalforum.org/whf_intro.html, diakses 12 September 2018).